Fraxetin attenuates disrupted behavioral and central neurochemical activity in a model of chronic unpredictable stress - Ahmed, Zainab; Tokhi, Ahmed; Arif, Mehreen; Rehman, Naeem Ur; Sheibani, Vahid; Rauf, Khalid; Sewell, Robert D. E. (Frontiers in Pharmacology, 2023)
Purpose: Chronic unpredictable stress (CUS) induces long-term neuronal and synaptic plasticity with a neurohormonal disbalance leading to the development of co-existing anxiety, depression, and cognitive decline. The side effects and delayed onset of current clinically used antidepressants has prompted a quest for antidepressants with minimum drawbacks. Fraxetin is a natural coumarin derivative with documented antioxidant and neuroprotective activity though its effects on stress are unknown. This study therefore aimed to investigate any possible acute effect of fraxetin in behavioral tests including a CUS paradigm in correlation with brain regional neurochemical changes. Methods: Mice were subjected to a series of mild stressors for 14 days to induce CUS. Furthermore, behavioral performance in the open field test, forced swim test (FST), Y-maze and elevated plus-maze were evaluated. Postmortem frontal cortical, hippocampal and striatal tissues were analyzed via high-performance liquid chromatography (HPLC) for neurochemical changes. Result: Acute administration of fraxetin (20-60 mg/kg, orally) decreased depression-like behavior in the FST and behavioral anxiety in both the open field test and elevated plus-maze. Memory deficits induced during the CUS paradigm were markedly improved as reflected by enhanced Y maze performance. Concurrent biochemical and neurochemical analyses revealed that only the two higher fraxetin doses decreased elevated serum corticosterone levels while diminished serotonin levels in the frontal cortex, striatum and hippocampus were reversed, though noradrenaline was only raised in the striatum. Concomitantly, dopamine levels were restored by fraxetin at the highest dose exclusively in the frontal cortex. Conclusion: Acute treatment with fraxetin attenuated CUS-induced behavioral deficits, ameliorated the increased corticosterone level and restored altered regional neurotransmitter levels and this may indicate a potential application of fraxetin in the management of anxiety and depression modeled by CUS. However, further studies are warranted regarding the chronic effects of fraxetin behaviorally and neurochemically.